Ethical risk assessment of coupled disaster of gas and coal fire in goaf - SI Junhong; CHENG Genyin; WANG Yiqiao; LI Lin; LI Yiman (Meikuang Anquan, 2023)
In the goaf of the high gas and spontaneous combustion coal seam, the gas drainage is mutually contradictory and restrictive to the prevention and control of coal spontaneous combustion. For this, we analyzed the disaster mechanism of gas and coal fire coupling disaster, determined the main factors affecting the coupling disaster, and identified the potential ethical risks of the existing gas and coal spontaneous combustion prevention technology. Based on analytic hierarchy process, the ethical risk assessment model of gas and coal fire coupling disaster was established and applied in 7436 working face of Kongzhuang Coal Mine. The results show that the weight of the coal spontaneous combustion during the mining of 7436 working face is 0.262 3, the weight of the gas disaster is 0.205 4, and the weight of the gas and coal fire coupling disaster is 0.529. Special attention should be paid to the occurrence of the gas and coal fire coupling disaster during mining. The probability of coal spontaneous combustion disaster is higher than that of gas disaster when coal spontaneous combustion disaster and gas disaster are treated respectively.